Childhood subacute inflammatory demyelinating polyneuropathy - Chia-Yu Hsu; Yao-Chia Chuang; Nan-Chang Chiu; Kuan-Wen Chen (Kaohsiung Journal of Medical Sciences, 2011)
Subacute inflammatory demyelinating polyneuropathy (SIDP) is an acquired immune-mediated peripheral polyneuropathy with clinical course between 4 weeks and 8 weeks. Rare childhood cases with SIDP had been described in the current literature. We report the first case of childhood SIDP in Taiwan with thorough clinical studies. All of the clinical presentations, laboratory data, electrophysiological studies, and image tools were compatible with childhood SIDP. Benign neurological recovery without relapse was correlated with electrophysiological evidence of demyelination predominantly.